EFEKTIVITAS PENERIMAAN PAJAK BUMI DAN BANGUNAN TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH KABUPATEN LAMONGAN (STUDI KASUS PADA KANTOR PEMERINTAHAN KABUPATEN LAMONGAN PERIODE TAHUN 2014 - 2018) - Dwihandoko, Toto Heru (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2020)
Tax is the source used to finance a development. One of which is the land and building tax. This study goals to determine (1) the effectiveness of land and building tax revenues in lamongan districts in 2014 until 2018, (2) barriers that impact the effectiveness of land and building tax revenues in the district of 2014 until 2018, (3) Government to overcome barriers that affect the level of tax effectiveness of the earth and buildings in the district lamongan 2014 until 2018. The method that used in this research is by documentation technique. Data analysis method used in this research is Quantitative Descriptive method. The results shows that: (1) the effectiveness of land and buildings tax revenues in the district of 2014 until 2018 has been very effective, (2) the barriers that impact the effectiveness of tax revenues of land and buildings is difficult to meet taxpayers, And knowledge of taxpayers in paying taxes, (3) efforts to overcome obstacles in the tax revenue of the land and buildings is in cooperation with village rayon coordinator, and held more socialization. The authors provide recommendations to the district revenue department of Lamongan district should more often hold socialization for tax revenue of land and buildings increasing in the years to come.